An educational program on nurses knowledge toward documentation in Al-Furat Alawsatt teaching hospital - Jebur, Hayder Ghaleb; Mohameed, Shatha Saadi (International journal of health sciences, 2022)
Nursing documentation is a component of clinical notes that nurses complete and is one of the most important sources of information in the health care profession. Because it serves so many different purposes, the patient record is one of the most important functions that a nurse performs. It contains all written information related to the patient's condition and needs.From September 21, 2020 to March 7, 2022, the researcher at Al-Furat Al-Awsat Teaching Hospital in Al-Najaf City used a quasi-experimental design with two groups and two evaluation stages to assess the effectiveness of the educational program in improving knowledge related to nursing documentation. A total of (50) nurses were randomly assigned to two groups and enrolled using non-probability deliberate selection procedures. One group was given the program (the study), while the other was not (the control group), and both groups were tested twice (pretest and posttest). Students from both groups showed insufficient knowledge (56 percent for the study and 72 percent for the observation). When students in the study group were compared after executing the program, (post-tests) demonstrated a significant improvement (p-value 0.001) in knowledge (68 percent).